Global capitalism and the nation state in the struggles over GM crops in Brazil - Campos Motta, Renata (Journal of agrarian change, 2016)
The introduction of biotechnology is part of a global process of structural change in agriculture characterized by an increased integration of world agriculture with high corporate control. However, as the legal competence to allow the planting and trade of genetically modified (GM) crops commonly lies at the level of the nation state, this remains strategic in the politics of GM crops, both for actors promoting the technology and for social movements struggling against it. This paper illustrates this argument with an analysis of the struggles over GM crops in Brazil. It shows how the implementation of a food regime based on biotechnology, corporate control and neoliberal globalism depended on the state and was a contested process.